PENGARUH FAKTOR INTRINSIK DAN FAKTOR EKSTRINSIK TERHADAP MOTIVASI PEGAWAI DI KECAMATAN METRO PUSAT KOTA METRO - Saeful Ramadhan Sobandi; Akhmad Suharyo; Azima Dimyati (Universitas Bandar Lampung (UBL), 2020)
The problems in this study are: (1) Is there an influence of Intrinsic Factors on Employee Motivation in Metro District in Metro City Centers? (2) Is there an Effect of Extrinsic Factors on Employee Motivation in Metro District, Metro City Center? (3) Is there a joint effect of Intrinsic Factors and Extrinsic Factors Against Employee Motivation in Metro District Metro City Center?The plan in this study is to use a survey method. By means of the census it is intended that all populations are also sampled because the population is limited and allows researchers to examine all populations using questionnaires as a data collection tool. explore the factors that cannot be revealed in the questionnaire..The results showed that there was a partial effect of intrinsic factors on employee motivation, as well as extrinsic factors influencing employee motivation. In Metro District Metro City Center, the greatest influence of the variables forming job satisfaction was the achievement dimension, while the smallest dimension of the variables forming intrinsic factor is the dimension of responsibility. Then the biggest dimension of the extrinsic factor is the Salary Dimension while the smallest dimension of the extrinsic factor variable is the working condition dimension.Intrinsic Factors and Extrinsic Factors together have a positive effect on Employee Motivation at the Central Metro District Office. The contribution of the Intrinsic Factor and Extrinsic Factors to Employee Motivation is in the moderate but not optimal category, this shows that there are still employees who have not fully carried out their duties properly. This happens because there are still outside variables that are influential but not examined.